2019
DOI: 10.1055/s-0039-1688799
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Study of Anatomical Variations in the Musculocutaneous Nerve and in the Median Nerve

Abstract: Introduction The musculocutaneous nerve and the median nerve are branches from the lateral cord of the brachial plexus with a root value of C5, C6, and C7. The medial root of the median nerve is a branch of the medial cord. The present study aims at observing any variations in these peripheral nerves, so that this knowledge can be utilized by surgeons, anesthesiologists, and orthopedicians during surgical procedures and nerve block. Materials and Methods The present study was carried on 30 adult em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…However, at times the subclavian-axillary stem is derived from the sixth or eighth segmental arteries establishing an abnormal relation about the cords of the brachial plexus [ 5 ]. As presented in Table 2 , our findings were similar to other North Indian studies [ 2 , 6 ]. However, a strikingly higher incidence was observed in Central Indian, Malaysia, Nepal populations, and lower incidence in Iranian and Sri Lankan populations [ 7 - 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, at times the subclavian-axillary stem is derived from the sixth or eighth segmental arteries establishing an abnormal relation about the cords of the brachial plexus [ 5 ]. As presented in Table 2 , our findings were similar to other North Indian studies [ 2 , 6 ]. However, a strikingly higher incidence was observed in Central Indian, Malaysia, Nepal populations, and lower incidence in Iranian and Sri Lankan populations [ 7 - 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…A branch of the median nerve was continued as a lateral cutaneous nerve of the forearm. According to this study, this was comparable to the right upper extremity case (10).…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our study Priya et al, reported the communication in 8 cases out of 60 (13.3%). Their study showed 5 communications on the left side and 3 on the right side 4. Studies done by Beheiry et al, Chitra et al, Joshi et al, Budhiraja et al, Dahiphale et al, Balachandra et al,…”
mentioning
confidence: 86%